Interactive virtual indoor navigation system using visual recognition and pedestrian dead reckoning techniques - Chin, Gee Low *; Lee, Yunli * (SERC, 2015)
Finding a destination in an unfamiliar indoor environment requires cumbersome effort to refer to a physical floor plan or directory to locate the intended destination. With the advancements of mobile technologies, a navigational system using mobile computing devices such as mobile phone or tablet could aid users in locating the desired destination with ease. This paper presented an interactive virtual indoor navigation system which is developed for Sunway University campus. In order to provide an interactive and context-sensitive navigation platform, a hybrid solution has been proposed by blending the sensor capabilities on the mobile devices to work in an indoor environment. These sensors include utilizing the built-in accelerometer, compass and camera capabilities to create an interactive content of indoor navigation system using visual recognition and pedestrian dead reckoning for Augmented Reality (AR). Furthermore, user satisfaction and feedback survey have been collected for further improvement the proposed solution.